Nanocomposite Strategy toward Enhanced Thermoelectric Performance in Bismuth Telluride - Zhuang, Hua‐Lu; Yu, Jincheng; Li, Jing‐Feng (Small science, 2025)
Bismuth telluride‐based thermoelectric (TE) materials have been commercially applied in near‐room temperature refrigeration. However, enhancing their TE performance remains crucial for expanding their application fields. Nanocomposite strategy has been widely reported as an effective approach to improving the TE performance of bismuth telluride‐based materials. In this review, the nanoinclusions are categorized into different groups, including nonmetallic hard nanoparticles, metallic nanoparticles, compounds with low thermal conductivity, and low‐dimensional materials. A comprehensive overview of relevant researches and present typical cases and recent advancements is provided. It is worth noting that nonmetallic hard nanoparticles are most widely used for reinforcing bismuth telluride‐based materials; the noticeable enhancement can be attributed to the interfaces that induce phonon scattering to reduce lattice thermal conductivity as well as multiple scattering effects along with energy filtering to increase the Seebeck coefficient. Although there exist challenges in terms of interface characterization and dispersion improvement for nanoinclusions, it is undeniable that the nanocomposite strategy offers a viable pathway to enhance the TE performance of bismuth telluride‐based materials. Therefore, further exploration in this direction is warranted to promote the development and application of TE technology at near‐room temperature. Nanocomposite strategy proves to be highly effective in enhancing the thermoelectric performance of bismuth telluride‐based materials, owing to the synergistic effect on charge carrier and phonon transport. This review comprehensively discusses the impact of various nanoinclusions on thermoelectric properties of bismuth telluride‐based materials, highlights the existing challenges, and presents promising prospects for future development of this strategy.